2021
DOI: 10.17811/rifie.50.2.2021.603-614
|View full text |Cite
|
Sign up to set email alerts
|

Language Teachers' Professional Development and New Literacies: An Integrative Review

Abstract: The aim of this paper is to synthesize the themes and topics addressed language teachers’ new literacies in the published articles between 2010–2020 to understand research and approaches to the new literacies of language teachers. To this end, the researchers applied an integrative review of 29 papers selected from a body of 503 published papers in nine databases. The review showed that most papers related to new literacies in professional development focused on the term digital literacy. Moreover, most of the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 87 publications
0
3
0
Order By: Relevance
“…During 2010-2020, research papers describing new literacies and teachers' professional development have been published (Tafazoli, 2021). Digital literacy is a necessary component of teachers' survival skills in the twenty-first century, and it must be considered while enhancing the capabilities of teachers, particularly language teachers.…”
Section: Professional Training Before and During Covid-19mentioning
confidence: 99%
“…During 2010-2020, research papers describing new literacies and teachers' professional development have been published (Tafazoli, 2021). Digital literacy is a necessary component of teachers' survival skills in the twenty-first century, and it must be considered while enhancing the capabilities of teachers, particularly language teachers.…”
Section: Professional Training Before and During Covid-19mentioning
confidence: 99%
“…Employing technology to improve teachers' professional development is a highly demanded practice within the field of teacher education (Tafazoli 2021). Particularly, video technology has been extensively used in this field over the past decades, and its use has increased in language teacher education due to its potential (Hüttner 2019).…”
Section: Introductionmentioning
confidence: 99%
“…Lo (2020) highlighted the importance of designing more professional development programmes for pre-and in-service teachers. Tafazoli (2021) concluded that it is necessary to train teachers with technologies to enhance their professional development.…”
Section: Introductionmentioning
confidence: 99%